2006
DOI: 10.1366/000370206778397434
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Tape-Lift Method and Fourier Transform Infrared Spectroscopic Imaging for Forensic Applications

Abstract: Conventional Fourier transform infrared (FT-IR) spectroscopy and microscopy have been widely used in forensic science. New opportunities exist to obtain chemical images and to enhance the spatial resolution using attenuated total reflection (ATR) FT-IR spectroscopy coupled with a focal-plane array (FPA) detector. In this paper, the sensitivity limits of FT-IR imaging using three different ATR crystals (Ge, ZnSe, and diamond) in three different optical arrangements for the detection of model particles is discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…The direct detection of contact residuals, within a fingermark has recently been demonstrated by the use of attenuated total reflectron (ATR) FT-IR spectroscopy/microscopy and desorption electrospray ionization mass spectrometry (DESI-MS). ATR FT-IR has been used to detect paracetamol, ibuprofen and diacetylmorphine residues, within the fingermark [7] and to image the distribution of endogenous Hydrophobic silica nanopowder has been used as an effective latent fingermark development agent and subsequently as an enhancement agent in the surface-assisted laser desorption/ionisation-time of flight (SALDI-TOF) mass spectrometry for analysis of fingermark components. The technique has been used in the detection of nicotine and cotinine in the fingermarks of smokers.…”
Section: Introductionmentioning
confidence: 99%
“…The direct detection of contact residuals, within a fingermark has recently been demonstrated by the use of attenuated total reflectron (ATR) FT-IR spectroscopy/microscopy and desorption electrospray ionization mass spectrometry (DESI-MS). ATR FT-IR has been used to detect paracetamol, ibuprofen and diacetylmorphine residues, within the fingermark [7] and to image the distribution of endogenous Hydrophobic silica nanopowder has been used as an effective latent fingermark development agent and subsequently as an enhancement agent in the surface-assisted laser desorption/ionisation-time of flight (SALDI-TOF) mass spectrometry for analysis of fingermark components. The technique has been used in the detection of nicotine and cotinine in the fingermarks of smokers.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Recently three new approaches have been described for the direct analysis of the constituents of fingermarks and of contact residues. The first employs attenuated total reflection FT-IR spectroscopy/microscopy, which has been used to detect contact residues of three drugs on the surface of a lifted mark [4] and to produce an image of the distribution of endogenous constituents within a fingermark. [5] The second method uses electrospray ionisation coupled with MS for direct analysis of contact residues, and to image their distribution within the surface of the fingermark.…”
Section: Introductionmentioning
confidence: 99%
“…For fingermark samples, m-FTIR is generally used in reflection or attenuated total reflection (ATR) modes, coupled with chemical imaging or not. The analysis of fresh fingermarks left on porous and non-porous substrates has been carried out by numerous authors, and better spectral quality has been reported for fingermarks left on metal and glass [26,27,[33][34][35][36][37]45,[53][54][55]. Further analyses have revealed that the main spectral features found in the fingermarks of various donors are very similar to each other, and correspond to esters and fatty acids.…”
Section: Introductionmentioning
confidence: 99%